Gereja Pilgrimasi: Menggagas Bentuk Keanggotaan Persekutuan Misional Diaspora dalam Pelayanan Gereja Toraja - Johana Ruadjanna Tangirerung; Dan Mangoki'; Agustinus Karurukan Sampeasang; Yonathan Mangolo (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Abstract. The church’s mission in a fluid world requires new spaces of service. If the church is not responsive and critical of its reality, it is difficult for the church to be present to answer the needs of the people. One interesting reality is the existence of the diaspora. The extent to which the church's mission reaches the diaspora as a missional space is a challenge. This paper aimed to propose a form of diaspora missional fellowship membership in the ministry of the Toraja Church. The method used was a qualitative method with observation survey technique through two congregations in Tana Toraja and North Toraja and interviews with purposive sampling technique to some specifically determined people. Through this research, it was concluded that pilgrimage churches confront the church with a way of doing church based on the spirit of pilgrimage, which crosses the boundaries of geography, territory and church walls.Abstrak. Misi gereja di dunia yang cair membutuh ruang-ruang pelayanan baru. Jika gereja tidak responsif dan kritis terhadap realitasnya, sulit bagi gereja hadir menjawab kebutuhan umat. Salah satu realitas menarik adalah keberadaan diaspora. Sejauh mana misi gereja menjangkau diaspora sebagai ruang missional menjadi sebuah tantangan. Tulisan ini bertujuan untuk mengusulkan bentuk keanggotaan persekutuan misional diaspora dalam pelayanan Gereja Toraja. Metode yang digunakan adalah metode kualitatif dengan teknik survey observasi melalui dua jemaat di Tana Toraja dan Toraja Utara dan wawancara dengan teknik purposive sampling terhadap beberapa orang yang ditentukan secara khusus. Melalui penelitian ini disimpulkan bahwa gereja pilgirimasi memperhadapkan gereja pada cara bergereja yang dilandasi oleh semangat peziarahan, yang melewati batas geografi, teritorial dan tembok-tembok gereja.